KOMPENSASI TERHADAP KINERJA GURU SMK - Lestari, Fitri; Rahmawati, Ima; Lestari, Hana; Ihsan, Muzhir (Institut Agama Islam Sahid (INAIS) Bogor, 2023)
The aim of this research is to describe the effect of compensation on teacher performance in private vocational schools, Kec. Pamijahan Bogor is accredited B. This research uses quantitative research. The data collected in the form of numbers was analyzed using simple linear regression analysis. The number of samples taken was 94 teachers, using a probability sampling method with a simple random sampling technique. The research method used is quantitative research with data collection techniques using questionnaires. The data analysis technique used is simple linear regression. Based on the regression test, a significant value of 0.000 <0.05 was obtained, so it can be concluded that there is a positive and significant influence between recruitment and compensation on teacher performance. This shows that the better the compensation provided, the better the optimal teacher performance will be. Therefore, to improve teacher performance, it is hoped that schools will pay more attention to the health of their teachers